Evaluation of the Impact of Video Media on Students’ Science Learning Outcomes - Erma Suryani Sahabuddin; Nurlita Pertiwi (AL-ISHLAH: Jurnal Pendidikan, 2023)
The increase in data innovation and correspondence is fundamentally affecting several areas of an individual's life. But the reality is that at this time, there are still many educators who have not been able to carry out a learning process that can develop students' thinking skills by using various media due to the learning process, both online and offline learning. The purpose of this research; to find out the description of the use of VIPE media on science learning and the effect of using VIPE media on learning outcomes. This research approach uses quantitative research with a quasi-experimental type. The population in this study was 180 students using purposive sampling. The data collection techniques use observation, tests, and documentation. The data analysis technique uses descriptive statistics and inferential statistics. The results of this study are that the learning process using VIPE media in the experimental class takes place effectively because the percentage category for each meeting increases. The first meeting was effective then the second meeting was very effective using VIPE media. And there is a positive influence on the use of VIPE media. This is because there are significant differences between the experimental class and the control class. This is because the probability value is smaller than 0.05. Therefore, the existence of this media gives appreciation to teachers who develop learning media to improve student learning outcomes, one of which is media in the form of learning videos.